2017
DOI: 10.1016/j.watres.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Potential water resource impacts of hydraulic fracturing from unconventional oil production in the Bakken shale

Abstract: Modern drilling techniques, notably horizontal drilling and hydraulic fracturing, have enabled unconventional oil production (UOP) from the previously inaccessible Bakken Shale Formation located throughout Montana, North Dakota (ND) and the Canadian province of Saskatchewan. The majority of UOP from the Bakken shale occurs in ND, strengthening its oil industry and businesses, job market, and its gross domestic product. However, similar to UOP from other low-permeability shales, UOP from the Bakken shale can re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(43 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…For example, the Weyburn-Midale field design eliminated the need for 115 tank batteries (Scott 1966). In North Dakota, where non-pipelined oil and gas operations evolved rapidly, 56% of Bakken crude oil is transported by truck and 44% is transported by pipeline (Shrestha et al 2017). We could not find similar statistics for Saskatchewan.…”
Section: Interpretationsmentioning
confidence: 71%
See 1 more Smart Citation
“…For example, the Weyburn-Midale field design eliminated the need for 115 tank batteries (Scott 1966). In North Dakota, where non-pipelined oil and gas operations evolved rapidly, 56% of Bakken crude oil is transported by truck and 44% is transported by pipeline (Shrestha et al 2017). We could not find similar statistics for Saskatchewan.…”
Section: Interpretationsmentioning
confidence: 71%
“…Of the 93 emitting unconventional sites, 88% included wells, and 22 had >1 well (μ=1.18, σ=0.74). Multi-well sites are common in this region and also the North Dakota Bakken, where multiple horizontal wells on the same pad increase the economic potential of unconventional oil (Shrestha et al 2017). At the well, emissions may originate from fugitive or vented sources at the wellhead stuffing box, or via surface casing vent flow (Lackey et al 2017).…”
Section: Site Characteristicsmentioning
confidence: 99%
“…Hydraulic fracturing with subsequent production from horizontal wells is used both in shale gas and in shale oil fields (Caper, 2010; Daly et al, 2016; Shrestha et al, 2017). A key difference is that shale oil production can also require injection of water for continued oil recovery (Laurenzi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A key difference is that shale oil production can also require injection of water for continued oil recovery (Laurenzi et al, 2016). Flowback waters obtained from shale gas fields are highly saline (Daly et al, 2016; Khan et al, 2016; Shrestha et al, 2017), as are produced waters obtained from shale oil fields (Strong et al, 2013). However, in the case of shale oil fields the salinity of produced water may change depending on the salinity of the injection water used (Shrestha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hazards and risks associated with owback and produced water include hazards associated with accidental spills, leaks, and other emissions. [8][9][10][11] Concerns also arise from the potential contamination of surface water and aquifers due to poor well construction or maintenance, disposal of spent uids, and disposal of uids generated during oil and gas production. 7, 12,13 Previous studies have investigated the phenomenon of owback in produced water from stimulated wells and found that water quality of the return-ow changed over time, typically with an initial composition (as indicated by total dissolved solids (TDS) or other chemical indicators) similar to the injected uid, with a gradual transition to more saline connate water.…”
Section: Introductionmentioning
confidence: 99%